Pengaruh Kebijakan Dividen, Profitabilitas dan Keputusan Investasi terhadap Nilai Perusahaan pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) - Rahmaneeyuda , Larasati; Andriana, Isni; Taufik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the impact of dividend policies, profitability, and investment decisions on the value of companies in the mining sector listed on the Indonesian Stock Exchange. This research uses quantitative data with a secondary data source obtained from the Indonesian Stock Exchange financial reports. Sampling in this study used purposive sampling techniques and obtained 10 companies as samples for research. The analysis technique used is linear regression analysis using SPSS 2.7. The results of the research show that Dividend Policy (DPR) and Investment Decisions (FATA) have no effect on the Company’s Value (PER), while rentability (ROA) has a significant negative impact on the company’s value. (PER).